A Review on the difference of physical and mechanical properties of bioplastic from seaweed hydrocolloids with various plasticizers. Issue 1 (January 2022) - Budiman, M A; Uju,; Tarman, K
Abstract: Seaweed hydrocolloids such as alginate and carrageenan extracted from brown and red algae have the potential to be developed as bioplastic. Bioplastic is a polymer from natural materials that are biodegradable. Alginate and carrageenan-based bioplastics are brittle and inelastic. Plasticizers such as glycerol, sorbitol and polyethylene glycol can be added to formulate plastic to improve its properties. The aim of the research was to review the physico-chemical properties of the bioplastic made from seaweed hydrocolloids with various additions of plasticizers. The data used in this study were taken from several accredited national journals and international publications. The data were presented quantitatively and synthesized narratively to answer the hypothesis of the study. The results showed that the addition of plasticizer in bioplastic preparation affected the physico-chemical properties of bioplastics. The thickness and elongation at break of bioplastic increased after the addition of plasticizers. However, the tensile strength of the bioplastic has decreased after added with plasticizer.